Microbial vs abiotic origin of methane in continental serpentinized ultramafic rocks: A critical review and the need of a holistic approach. (August 2022) - Etiope, Giuseppe; Oze, Christopher
Abstract: Continental ultramafic rock systems, through the process of serpentinization, provide chemical and biochemical pathways that lead to the production of methane. The extent to which rock-water-gas reactions and organisms supply methane in these systems is a matter of considerable discussion and debate. Deciphering the interplay of abiotic and microbial methane observed at the surface requires several lines of reasoning as well as a variety of analyses. Despite using multiple models and interpretative tools, conclusions for the origin of methane at a particular site may vary or diverge from regional or global observations. Here, we critically address how possible conclusions of microbial versus abiotic methane in continental serpentinization systems may be interpreted and reinterpreted. We review fundamental concepts, advantages and limits, for three major methane origin models: (a) abiotic CO2 hydrogenation supplying gas reservoirs, (b) derivation from fluid inclusions in olivine-rich rocks, and (c) microbialgenesis in aquifers. We use the case of methane in the Samail ophiolite of Oman as an emblematic example of multiple interpretations; we identify ambiguous information offered by methane clumped isotopes and molecular gas compositions (e.g., the meaning of gaseous hydrocarbons heavier than methane), and suggest key tools, such as radiocarbon ( 14 C) in methane, which may solve interpretative issues. The major constraint in any model of methane origin is the capability to sustain continuous gas flows, in terms of methane emission intensity, longevity and spatial extension, such as in natural gas sedimentary systems. Overall, this review suggests that any site interpretation can benefit from a holistic approach, integrating geochemical, geological and biological data with gas flow dynamics, as well as including regional and global contextualization. Highlights: Pros and cons of abiotic and microbial hypotheses of CH4 in ultramafic rock systems. CH4 clumped-isotopes of microbial and abiotic gas overlap. 14 C-methane as a key, but neglected, diagnostic parameter. CH4 genetic models must be compatible with gas flow dynamics constraints. Need of a holistic contextualization of local observations.